The influence of the waterlogging in the death of peach and plum trees - Guerra, Lauri José; Finard, Nelson Luiz; Filho, Benedito Gomes dos Santos; Peters, José Antônio (Pesquisa Agropecuaria Brasileira, 1992)
A series of experiments were run to study the effects of flooding on potted peach and plum seedlings of the two local peach (Prunus persica, Batsch.) cultivars Capdeboscq and Magno and of the plum (Prunus salicina, Lindl.) cultivars Santa Rosa and Harry Pickstone, to test about their sensitivity to flooding. Vegetating plants were more sensitive than dormant plants. Peach trees were more sensitive than plum trees. It was observed that the plants that had higher tolerance to flooding emitted higher number of adventitious roots and had more severe hypertrophy of the submerged lenticels. Also peach plantlets, when waterlogged for 86 days, showed this relation between lenticels hypertrophy and flood tolerance.